EphrinB2-EphB4-RASA1 Signaling in Human Cerebrovascular Development and Disease. Issue 4 (April 2019) - Zeng, Xue; Hunt, Ava; Jin, Sheng Chih; Duran, Daniel; Gaillard, Jonathan; Kahle, Kristopher T.
Abstract : Recent whole exome sequencing studies in humans have provided novel insight into the importance of the ephrinB2-EphB4-RASA1 signaling axis in cerebrovascular development, corroborating and extending previous work in model systems. Here, we aim to review the human cerebrovascular phenotypes associated with ephrinB2-EphB4-RASA1 mutations, including those recently discovered in Vein of Galen malformation: the most common and severe brain arteriovenous malformation in neonates. We will also discuss emerging paradigms of the molecular and cellular pathophysiology of disease-causing ephrinB2-EphB4-RASA1 mutations, including the potential role of somatic mosaicism. These observations have potential diagnostic and therapeutic implications for patients with rare congenital cerebrovascular diseases and their families. Highlights: Genetic and functional studies in model organisms have revealed the importance of ephrinB2-EphB4-RASA1 signaling in multiple aspects of cerebrovascular development. Recent whole exome sequencing studies in humans have identified mutations in EFNB2, EPHB4, and RASA1 in multiple congenital cerebrovascular disorders. These diseases include capillary malformation-arteriovenous malformation (CM-AVM), Vein of Galen malformation (VOGM), and others. The localized nature and multifocality of lesions associated with ephrinB2-EphB4-RASA1 mutations implicates somatic mosaicism in disease pathogenesis. The ephrinB2-EphB4-RASA1 axis is a potentially targetable node for therapeutic intervention.